Scope of State in Legislation from Islamic Perspective - Farhadullah; Fazle Omar (Journal of Islamic and Religious Studies, 2017)
Islamic law is basically a part of a holistic system based primarily on the divine message enclosed in the Holy Qur'an and traditions of the Prophet (SAW), which are the main fundamental sources of Islamic law. After the demise of the Prophet (SAW), field of Ijtehād started development, which was already approved by the Prophet (SAW) in his life. The companions of the Prophet (SAW) developed the notion of Ijmā while early Muslim jurists discovered the Qiyās, Maslaha, Istislāh, Istehsān etc.Determining the location of authority and its scope in law-making has remained a complex situation for the western philosophers since long. As far as the case of Muslims is concerned, they are in the position to find solution of this situation as to where the authority dwells; enabling them to resolve many queries which seemed to be unanswered for the long time. It is important for the Muslims to comprehend the concept of Islamic institutions from the perspective of Islamic frame work and legal as well as constitutional history of Islamic history.